(untitled) (Research, Society and Development, 2024)
Objective: To identify the correlation between the misuse of safety equipment and its relationship with traumatic brain injury in pediatric patients in traffic accidents. Methods: Searches were carried out in the databases of platforms such as SciELO, PubMED and selected scientific journals to carry out an integrative review published in the last eight years that addressed the severity of pediatric TBI with the incorrect and/or inadequate use of safety equipment. Results: When preparing the article, 11 studies were selected that addressed the correlation between the inappropriate use of traffic safety equipment by pediatric patients with increased morbidity and mortality and increased health expenditure. Final considerations: The systematic review identified that the negligence and recklessness of parents when transporting pediatric patients contribute to the worse prognosis in automobile accidents, due to the greater mechanical energy in the trauma that leads to serious conditions such as, for example, intracranial hematoma and axonal injury diffuse. Therefore, the following study aims to demonstrate the importance of monitoring and disseminating information on the subject in order to avoid such events.